Zmiany pozycji Polski w gospodarce światowej po 1990 roku - Chrzan, Mariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The author evaluates in this paper the position of Poland in the world economy. First, the relation of Polish GDP per capita in 1929 to the reported levels in some selected countries had been examined. Furthermore, the similar comparisons had been made for the years 1990 and 2006. The author found out, that the GDP gap between Poland and the most advanced economies increased significantly within the period 1930-1996. This was one of the consequences of the decades of the inefficient central planed economy. The accelerated economic growth in the years 1990-2006 made it possible to reduce the GDP gap back to the relations of the year 1929. Although Poland registered the highest average growth rate of all reported countries, the data for the last couple of years are substantially worse. To restore higher dynamic of its economy Poland needs institutional reforms, reasonable monetary policy and smooth absorption of European structure funds. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 63-69